PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) DENGAN MEDIA GAMBAR UNTUK PENINGKATAN HASIL BELAJAR PECAHAN SISWA KELAS IV SDN 1 BANDUNG TAHUN AJARAN 20012/2013 - maisaroh, Dwi Rofi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Cooperative Learning Type NHT (Numbered Heads Together) with Images Media for Improved Learning Outcomes Smithers fourth Grade Students Elementary School Bandung 1 in Year 2012/2013. This study aimed to describe: (1) the application of cooperative learning with media images Numbered Heads Together for yield enhancement learn about fractions Elementary School fourth grade students. (2) the constraints and solutions application of cooperative learning type Numbered Heads Together with images media for yield enhancement learn about fractions Elementary School fourth grade students. The subjects were fourth grade students of Elementary School year 2012/2013 a total of 36 students. The experiment was conducted in three cycles, with each cycle consisting of planning, action, observation, and reflection. Techniques of collecting data through observation, interviews, test and documentation. The results show that application of cooperative learning with images media Numbered Heads Together can improve learning outcomes of fractions Elementary School fourth grade students. Keywords: NHT, image media, learning fraction outcomes. Abstrak: Penerapan Pembelajaran Kooperatif Tipe NHT (Numbered Heads Together) dengan Media Gambar untuk Peningkatan Hasil Belajar Pecahan Siswa Kelas IV SDN 1 Bandung Tahun Ajaran 2012/2013. Penelitian ini bertujuan untuk (1) mendeskripsikan: (1) penerapan pembelajaran kooperatif tipe NHT dengan media gambar untuk peningkatan hasil belajar tentang pecahan siswa kelas IV SD. (2) kendala dan solusi penerapan pembelajaran kooperatif tipe NHT dengan media gambar untuk peningkatan hasil belajar tentang pecahan kelas IV SD. Subjek penelitian adalah siswa kelas IV SDN 1 Bandung TA 2012/2013 berjumlah 36 siswa. Penelitian dilaksanakan dalam tiga siklus, terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Teknik pengumpulan data dengan tes, observasi, wawancara, dan dokumentasi. Hasilnya menunjukkan bahwa penerapan pembelajaran Kooperatif tipe NHT dengan media gambar dapat meningkatkan hasil belajar tentang pecahan siswa kelas IV SD. Kata Kunci: NHT, media gambar, hasil belajar pecahan.